Spatial and temporal patterns of water salinity in the marginal grabens of Ethiopia's Danakil Depression. (23rd June 2019) - Meaza, Hailemariam; Hermans, Laurens; Nyssen, Jan; Frankl, Amaury; Zenebe, Amanuel; Demissie, Biadgilgn; Asfaha, Tesfaalem Ghebreyohannes; Van Eetvelde, Veerle; Deckers, Jozef; Poesen, Jean
Abstract: Rising salinity is a severe problem associated with land degradation in arid and semiarid regions. This study seeks to understand the spatiotemporal patterns of water salinity and their implication on the downstream water availability in the marginal grabens of northern Ethiopia. We measured the electrical conductivity (EC) of flash floods, baseflows, springs, wells, and lakes. A total of 1, 168 samples was collected from 177 spatially distributed water sources (2016–2017). This study shows that there was a significant difference in the EC values of the water points between rainy (1, 403 ± 425 μS cm −1 ) and dry seasons (2, 261 ± 258 μS cm −1 ). Besides, there is an inverse relationship between the river discharges and the runoff EC in the study area. The average value of the water EC was also higher in the limestone area than in the basalt sites. In addition, the water EC increased from the escarpments (396 ± 176 μS cm −1 ) towards the outlets of the graben basins (1, 670 ± 942 μS cm −1 ). These water EC hotspots in the dry season imply that the river basins are in a closing status due to the erratic rainfall and water extraction by humans. However, the rising water EC and moisture stress endanger the existing agricultural development. Because of the extent and seriousness of salinity, integrated catchment management strategies are needed to tackle the degrading water quality and quantity in the marginal grabens along the northern Ethiopia Rift Valley.